Plate-Assisted Intramedullary Nailing of Gustilo Type IIIB Open Tibial Diaphyseal Fractures: Does Adjunctive Plate Retention Affect Complication Rate?. Issue 7 (July 2020) - Stoddart, Michael T.; Al-Hourani, Khalid; Fowler, Tim; Khan, Umraz; Kelly, Michael B.
Abstract : Objectives: To investigate the complication rates after use of retained adjunctive plate (RAP) fixation with intramedullary nailing of Gustilo–Anderson type IIIB open tibia fractures, as part of a 2-stage orthoplastic approach. Design: Consecutive cohort study. Patients/Participants: One hundred and thirty-seven consecutive patients with a Gustilo–Anderson type IIIB open diaphyseal tibia fracture (OTA/AO 42) treated between May 2014 and January 2018. Ninety-eight patients (RAP = 67; non-RAP = 31) met the inclusion criteria and underwent 2-stage reconstruction. All patients were treated using a small fragment adjunctive plate to hold the fracture reduced before intramedullary nailing. Intervention: At stage 2, the temporary small fragment (in-fix) plate was removed and the site further thoroughly debrided. After this, the fracture is reduced and held with a new small fragment plate to facilitate the definitive intramedullary nailing. This new plate was either retained (RAP) as part of the definitive fixation at second stage or removed before wound coverage. Main Outcome Measurement: The main outcome measures were reoperation rate, deep infection, nonunion, and flap-related complication. Results: Six patients (6/98, 6.1%) proceeded to nonunion (RAP 5/67, non-RAP 1/31). This was not significant ( P = 0.416). Two hundred twelve operations were undertaken, and the median was 2. Sixteen (16/212, 7.5%) complication-related reoperations were undertaken, affecting 8 patients (8/67, 11.9%) in the RAP group. Eight patients (8/98, 8.2%) developed a deep infection (RAP 6/67, non-RAP 2/31). This was not significant ( P = 0.674). Conclusions: In the context of an orthoplastic approach, the use of a RAP with definitive intramedullary nailing does not seem to significantly increase the rate of deep infection or nonunion in patients with type IIIB open tibial shaft fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.